Physico-chemical assessment of natural sweeteners steviosides produced from stevia rebudiana bertoni plant - Abou-Arab, Esmat A.; Abou-Arab, Azza A.; Abu-salem, Ferial M. (2009)
The present study was conducted to reveal and shed more light on the effect of some technological process on the production of natural sweeteners steviosides from Stavia rebaudiana 8mtoni, Besides, physico-chemical and organolyptic properties of produced steviosides as substitute of sugar (sucrose) were studied.
Includes reference.
Summary in Arabic.
1
Keywords: Natural sweeteners -- Analysis; Stevia rebaudiana